Wii Fit™ exercise therapy for the rehabilitation of ankle sprains: Its effect compared with physical therapy or no functional exercises at all. Issue 7 (16th June 2015) - Punt, I. M.; Ziltener, J.‐L.; Monnin, D.; Allet, L.
Abstract : Lateral ankle sprains represent the most common sports‐related injuries. The Nintendo Wii Fit™ could be useful in the treatment of ankle sprains. The aim of this study was to compare the effectiveness of exercise training using the Wii Fit™ in ankle sprain patients: (a) with physical therapy; and (b) a control group not receiving any treatment. Ninety lateral ankle sprain patients were randomized to a Wii Fit™, physical therapy, or control group. We assessed the following outcome measures before, and 6 weeks after starting the allocated treatment: Foot and Ankle Ability Measure, pain during rest and walking, delay before return to sport, patient satisfaction, and effectiveness of the allocated treatment. Six weeks after the baseline measures, foot and ankle ability scores had improved in all groups, and pain had decreased during walking ( P < 0.050). No between‐group differences were detected between Wii Fit™ treatment, and both other groups ( P > 0.050). In conclusion, the Wii Fit™ could be used as an exercise therapy to treat ankle sprain patients. However, Wii Fit™ was not more effective than only physical therapy, or no exercise therapy at all. Patients who did not receive treatment showed similar results as people who got any kind of exercise therapy.